Inside, outside, and online : building your library community - Hill, Chrystie (American Library Association, 2009)
Inside, Outside, and Online provides practical advice and inspiration for building community with your library. Based on a scan of the community and technology environments within which libraries operate, related literature, and the practical experiences of hundreds of library staff, actively building communities through their work, the book provides much-needed insights into the essential elements of community building through identifying user needs and designing services to meet those needs; engaging communities with service selection, creation, and iteration; and utilizing practical new technologies. Whatever your role, and whatever the size or type of your library, the principles outlined here can support anyone working to build a strong community of engaged, interested, and satisfied library users.